2017
DOI: 10.1038/ngeo2899
|View full text |Cite
|
Sign up to set email alerts
|

Carbon sequestration in the deep Atlantic enhanced by Saharan dust

Abstract: 11ocean can potentially increase carbon uptake and sequestration at depth. Nutrients can 12 enhance primary productivity, and mineral particles act as ballast, increasing sinking 26Flux of airborne desert dust into the surface ocean can increase the amount of 27 photosynthetically fixed carbon dioxide (CO2) by reducing nutrient limitation of primary 28 production and thus increase the flux of particulate organic carbon (POC) to the deep ocean 1 . 29Dense dust-derived lithogenic particles can also increase par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
90
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 80 publications
(78 reference statements)
9
90
0
Order By: Relevance
“…therein;Okin et al, 2011). The fertilizing potential of Saharan dust is supported by previous studies in the Amazon Basin (Mahowald et al, 2008(Mahowald et al, , 2009Bristow et al, 2010), the Gulf of Mexico and the coast of southern Florida (Walsh et al, 2006;Lenes et al, 2012), and the North Atlantic subtropical gyre (Pabortsava et al, 2017). In addition to Saharan dust inputs, N 2 fixation by marine diazotrophs (Carpenter et al, 1999) and the seasonal discharge and eastward advection of the nutrient-enriched Amazon River Plume (e.g.…”
Section: Introductionsupporting
confidence: 58%
See 3 more Smart Citations
“…therein;Okin et al, 2011). The fertilizing potential of Saharan dust is supported by previous studies in the Amazon Basin (Mahowald et al, 2008(Mahowald et al, , 2009Bristow et al, 2010), the Gulf of Mexico and the coast of southern Florida (Walsh et al, 2006;Lenes et al, 2012), and the North Atlantic subtropical gyre (Pabortsava et al, 2017). In addition to Saharan dust inputs, N 2 fixation by marine diazotrophs (Carpenter et al, 1999) and the seasonal discharge and eastward advection of the nutrient-enriched Amazon River Plume (e.g.…”
Section: Introductionsupporting
confidence: 58%
“…High fluxes of organic material recently observed in a sediment trap in the North Atlantic subtropical gyre (23 • N, 41 • W) have been associated with enhanced phytoplankton productivity resulting from stimulated nitrogen fixation by Trichodesmium species following the deposition of dust-derived nutrients (Pabortsava et al, 2017). The role of aeolian dust for nitrogen fixation in subtropical and tropical oligotrophic regions has been previously reported by several authors (e.g.…”
Section: Influence Of Saharan Dust Depositionmentioning
confidence: 69%
See 2 more Smart Citations
“…So far, no studies have observed an influence from ballast minerals on microbial degradation (Ploug et al a,b ; Iversen and Ploug ; Iversen and Robert ), suggesting that the increased aggregate formation and higher sinking velocities may lead to an increased POC flux in dusty regions. This effect was directly shown in mesocosm experiments in the Mediterranean Sea, where an input of Saharan dust resulted in two to six times higher POC flux (Bressac et al ), and indirectly with sediment traps recording increased POC fluxes with dust deposition (Ternon et al ; Fischer et al ; Pabortsava et al ). Our results show that dust deposition caused a 10‐fold increase in total aggregated volume and two‐fold higher size‐specific sinking velocities of the dust‐ballasted aggregates.…”
Section: Discussionmentioning
confidence: 85%